Synthesis and properties of S-derivatives of 4-amino-5-(5-methylpyrazol-3-yl)-1,2,4-triazole - Fedotov, S. O.; Hotsulia, А. S.; Фeдотов, Сергій Олегович; Гоцуля, Андрій Сергійович; Фeдoтoв, С. O.; Гоцуля, А. С. (Запорізький державний медичний університет, 2021)
The combination of various heterocyclic systems with a wide range of properties is quite expedient and is, in practice, a justified direction for obtaining biologically active substances, which ultimately forms a favorable basis for the creation of drugs. In recent decades, the attention of scientists has been closely focused on nitrogen-containing heterocyclic compounds. Among such compounds, 1,2,4-triazole and pyrazole occupy a special place. Indeed, on the basis of these systems, a significant number of well-known drugs have been created, which are widely used at the present time. The aim of the work was the synthesis of S-derivatives of 4-amino-5-(5-methylpyrazol-3-yl)-1,2,4-triazole-3-thiol, study of their physical and chemical properties, pre-screening studies with subsequent establishment of the feasibility of further pharmacological studies. Materials and methods. Experimental methods of organic chemistry: synthesis using microwave activation, physical and chemical methods for the analysis of organic compounds (determination of the melting point, elemental analysis, 1H NMR, IR spectroscopy and chromatography-mass spectrometry). Methods for in silico pre-screening studies to establish the biological potential in several synthesized compounds (molecular docking). Results. 10 new S-derivatives of 4-amino-5-(5-methylpyrazol-3-yl)-1,2,4-triazole-3-thiol were synthesized. The structure of the obtained compounds was confirmed by a set of physical and chemical methods of analysis. According to the results of prescreening studies, the main directions of research of biological properties of synthesized compounds were provided. Conclusions. The expediency of using microwave irradiation in the synthesis of a series of S-alkyl derivatives of 4-amino-5-(5-methylpyrazol- 3-yl)-1,2,4-triazole-3-thiol had been proved. Based on the results of in silico studies, the expediency of further studies of anti-inflammatory, antifungal and anticancer activities in several synthesized compounds had been substantiated. Доцільним є поєднання різноманітних гетероциклічних систем із широким набором властивостей, оскільки це практично виправданий напрям одержання біологічно активних субстанцій, що формує підґрунтя для створення лікарських засобів. В останні десятиліття увага науковців прикута до нітрогеновмісних гетероциклічних сполук. Особливе місце з-поміж них посідають 1,2,4-тріазол і піразол, адже на основі цих систем створено чимало відомих лікарських засобів, що нині доволі широко використовують. Мета роботи – синтез S-похідних 4-аміно-5-(5-метилпіразол-3-іл)-1,2,4-тріазол-3-тіолу, вивчення їхніх фізико-хімічних властивостей, здійснення прескринінгових досліджень зі встановленням доцільності фармакологічних досліджень. Матеріали та методи. Застосували експериментальні методи органічної хімії: синтез із використанням мікрохвильової активації, фізико-хімічні методи аналізу органічних сполук (визначення температури плавлення, елементний аналіз, 1Н ЯМР, ІЧ-спектроскопія та хромато-мас-спектрометрія). Здійснили прескринінгові дослідження in silico для встановлення біологічного потенціалу в ряду синтезованих сполук (молекулярний докінґ). Результати. Встановили оптимальні умови одержання 10 нових S-похідних 4-аміно-5-(5-метилпіразол-3-іл)-1,2,4-тріазол-3-тіолу з використанням мікрохвильового опромінення. Будову сполук підтвердили комплексом фізико-хімічних методів аналізу. За результатами прескринінгового аналізу визначили основні напрями досліджень біологічних властивостей синтезованих сполук. Висновки. Доведено доцільність застосування мікрохвильового опромінення під час синтезу ряду S-алкілпохідних 4-аміно-5-(5- метилпіразол-3-іл)-1,2,4-тріазол-3-тіолу. У результаті дослідження in silico обґрунтовано доцільність вивчення протизапальної, протигрибкової та протиракової активностей у ряду синтезованих сполук. Целесообразно сочетание различных гетероциклических систем с широким набором свойств, так как это оправданное на практике направление получения биологически активных субстанций. В итоге это формирует основу для создания лекарственных средств. В последние десятилетия внимание учёных приковано к азотсодержащим гетероциклическим соединениям. Особое место среди них занимают 1,2,4-триазол и пиразол, ведь на основе этих систем было создано значительное количество известных лекарственных средств, которые достаточно широко используют. Цель работы – синтез S-производных 4-амино-5-(5-метилпиразол-3-ил)-1,2,4-триазол-3-тиола, изучение их физико-химических свойств, проведение прескрининговых исследований с установлением целесообразности дальнейших фармакологических исследований. Материалы и методы. Применили экспериментальные методы органической химии: синтез с использованием микроволновой активации, физико-химические методы анализа органических соединений (определение температуры плавления, элементный анализ, 1Н ЯМР, ИК-спектроскопия и хромато-масс-спектрометрия). Провели прескрининговые исследования in silico для установления биологического потенциала в ряду синтезированных соединений (молекулярный докинг). Результаты. Установлены оптимальные условия получения 10 новых S-производных 4-амино-5-(5-метилпиразол-3-ил)-1,2,4-триазол-3-тиола с использованием микроволнового облучения. Строение полученных соединений подтверждено комплексом физико-химических методов анализа. По результатам прескринингового анализа определены основные направления исследований биологических свойств синтезированных соединений. Выводы. Доказана целесообразность применения микроволнового облучения при синтезе ряда S-алкилпроизводных 4-амино-5-(5-метилпиразол-3-ил)-1,2,4-триазол-3-тиола. По результатам исследования in silico обоснована целесообразность дальнейшего изучения противовоспалительной, противогрибковой и противораковой активностей в ряду синтезированных соединений.
Синтез і властивості S-похідних 4-аміно-5-(5-метилпіразол-3-іл)-1,2,4-тріазол-3-тіолу
Синтез и свойства S-производных 4-амино-5-(5-метилпиразол-3-ил)-1,2,4-триазол-3-тиола
Fedotov S. O. - ORCID ID: 0000-0002-0421-5303; Hotsulia A. S - ORCID ID: 0000-0001-9696-221X.
Keywords: 5-methylpyrazole; 1,2,4-triazole; synthesis; properties; molecular docking; 5-метилпіразол; 1,2,4-тріазол; синтез; властивості; молекулярний докінґ; 5-метилпиразол; 1,2,4-триазол; свойства; молекулярный докинг